Strategi komunikasi lingkungan Pemerintah Kota Pekanbaru pada pengerjaan proyek IPAL dalam menanggapi keluhan Masyarakat Kota Pekanbaru - Rahmadi Rahmadi; Agung Prawoto; Diana Sari; Kaheta Mandasari; Maizul Hardinas; M Rizki; Nia Ramadani; Muhammad Firdaus (Pelantar Press, 2022)
A healthy environment is very important for people's lives, especially in urban areas. Pekanbaru City is one of the cities in Indonesia that is working on the Wastewater Treatment Plant (WTP) project. However, there are development constraints in the surrounding environment. Many parties expressed dissatisfaction with the idea of the Pekanbaru city government. Congestion, economy, road damage, property damage, and environmental problems caused by dust and water during the project are. The problem that has occurred is one example of an environmental communication study that requires stakeholder participation to be resolved. The purpose of this research is to identify the environmental pollution caused and the Government's communication strategy in responding to this problem.